Enhanced Dibutyl Phthalate Sensing Performance of a Quartz Crystal Microbalance Coated with Au-Decorated ZnO Porous Microspheres - Zhang, Kaihuan; Fan, Guokang; Hu, Ruifen; Li, Guang (Sensors (Basel, Switzerland), 2015)
Noble metals addition on nanostructured metal oxides is an attractive way to enhance gas sensing properties. Herein, hierarchical zinc oxide (ZnO) porous microspheres decorated with cubic gold particles (Au particles) were synthesized using a facile hydrothermal method. The as-prepared Au-decorated ZnO was then utilized as the sensing film of a gas sensor based on a quartz crystal microbalance (QCM). This fabricated sensor was applied to detect dibutyl phthalate (DBP), which is a widely used plasticizer, and its coating load was optimized. When tested at room temperature, the sensor exhibited a high sensitivity of 38.10 Hz/ppb to DBP in a low concentration range from 2 ppb to 30 ppb and the calculated theoretical detection limit is below 1 ppb. It maintains good repeatability as well as long-term stability. Compared with the undecorated ZnO based QCM, the Au-decorated one achieved a 1.62-time enhancement in sensitivity to DBP, and the selectivity was also improved. According to the experimental results, Au-functionalized ZnO porous microspheres displayed superior sensing performance towards DBP, indicating its potential use in monitoring plasticizers in the gaseous state. Moreover, Au decoration of porous metal oxide nanostructures is proved to be an effective approach for enhancing the gas sensing properties and the corresponding mechanism was investigated.